Nutrient Enrichment Increases Grassland Biomass Sensitivity to Interannual Precipitation Variation - Ingrid J. Slette; Eric W. Seabloom; Carlos Alberto Arnillas; Jonathan D. Bakker; Dana Blumenthal; Jane A. Catford; Scott L. Collins; Nico Eisenhauer; Philip A. Fay; Magda Garbowski; Sylvia Haider; W. Stanley Harpole; et al. (Global Change Biology, 2026)
Primary production underpins much of ecosystem functioning and is often limited by nutrient and water availability. Ongoing global increases in nutrient inputs and interannual precipitation variability are thus likely to impact primary production, with unclear consequences for interannual variability in plant biomass. We used data from 35 grasslands in the Nutrient Network coordinated fertilization experiment to test if nutrient addition alters the response of plant biomass to year‐to‐year variation in growing season precipitation, and whether the effects of nutrient addition vary with factors such as site aridity or plant community composition. Nutrient addition increased biomass (by an average of 46% across sites), rain‐use efficiency (by 48%), and the sensitivity of biomass to interannual variation in precipitation (i.e., larger increase in biomass in wet years; by 13%), but did not change the strength of the interannual precipitation‐biomass correlation. Both sensitivity and correlation strength were higher in more arid sites, regardless of nutrient addition. These results suggest that grassland ecosystem functioning may become more variable from year to year as nutrient enrichment increases biomass sensitivity to precipitation and precipitation becomes more variable.

Global patterns and regional insights into kelp forest protection, restoration, and stewardship - Aaron M. Eger; Adriana Verges; Akshata MehtaFalkland Islands; Albert Pessarrodona; Alejandra Mora-Soto; Alejandro Bernal-Ibáñez; Aleksandra Smorygo; Alexandria M. Niese; Alexis Savard-Drouin; Andrew Kalani Carlson; Ang Put; Annalisa Falace; et al. (Journal of Applied Phycology, 2026)
Kelp forests are among the most extensive and productive coastal ecosystems, yet they remain underrepresented in global conservation policy despite widespread declines driven by interacting global- (i.e., ocean warming, marine heatwaves) to local-scale stressors. At the same time, kelp conservation and restoration efforts are expanding rapidly across regions, but measures of success and syntheses tend to primarily focus on ecological conditions and trends, not on conservation and restoration actions. To fill this gap, we developed a comparative global dataset of kelp conservation initiatives based on expert-derived regional narratives from 209 participants spanning 35 regions with kelp forests. We applied a structured presence–absence scoring framework across six domains: conservation actions, restoration approaches, governance actors, conservation objectives, social dimensions, and funding structures, supplemented by regional expert knowledge to enable cross-regional comparison. Across regions, conservation was characterised by strong emphasis on monitoring (86% of regions), multi-actor governance (scientific institutions 94%, government agencies 86%), and protecting existing forests (66%), while active restoration was undertaken in half of the regions. Social engagement (66%) and links to fisheries and livelihoods (69%) were widespread, whereas explicit climate adaptation objectives were less common (17%). We identify a set of conservation profiles that describe how kelp forest conservation is advancing in different ecological and governance contexts worldwide. These findings highlight that scaling kelp conservation is as dependent on the social, financial, institutional, and policy systems that govern implementation, as it is on ecological knowledge and technical capacity. By bridging regional knowledge with global analysis, this study provides a framework for aligning locally grounded conservation action with global biodiversity targets.

Socio-spatial constraints and facilitators of racially and ethnically diverse park visitation: A case study of U.S. urban park agency directors - Sammie L. Powers; Nicholas A. Pitas; Maggie Daniels; Nicole Webster; Andrew J. Mowen (Urban Forestry & Urban Greening, 2025)

Assessing the chemical burden of the North-East Atlantic ecosystem through targeted and untargeted HRMS-based approaches - Georgios Gkotsis; Maria-Christina Nika; Nikiforos Alygizakis; Konstantinos Vasilatos; Antonia Athanasopoulou; Jonathan L. Barber; Rob Berbee; Thierry Burgeot; Susana Galante Oliveira; Johan Gustafsson; Alejandro Iglesias Campos; Ulrike Kammann; et al. (Journal of Hazardous Materials, 2025)

Microbial source tracking in a coastal residential canal system - Nicole C. Powers; Anna Gitter; Nora Bleth; Andrew Johnson; Jacqueline Nicolay; Ray Ayers; Jeffrey W. Turner (Science of The Total Environment, 2025)

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

Data space inversion for efficient predictions and uncertainty quantification for geothermal models - Alex de Beer; Andrew Power; Daniel Wong; Ken Dekkers; Michael Gravatt; Elvar K. Bjarkason; John P. O’Sullivan; Michael J. O’Sullivan; Oliver J. Maclaren; Ruanui Nicholson (Computers & Geosciences, 2025)

TRPC Channels Activated by G Protein-Coupled Receptors Drive Ca2+ Dysregulation Leading to Secondary Brain Injury in the Mouse Model - Jasneet Parmar; Georg von Jonquieres; Nagarajesh Gorlamandala; Brandon Chung; Amanda J. Craig; Jeremy L. Pinyon; Lutz Birnbaumer; Matthias Klugmann; Andrew J. Moorhouse; John M. Power; Gary D. Housley (Translational Stroke Research, 2024)
Canonical transient receptor potential (TRPC) non-selective cation channels, particularly those assembled with TRPC3, TRPC6, and TRPC7 subunits, are coupled to G αq -type G protein-coupled receptors for the major classes of excitatory neurotransmitters. Sustained activation of this TRPC channel-based pathophysiological signaling hub in neurons and glia likely contributes to prodigious excitotoxicity-driven secondary brain injury expansion. This was investigated in mouse models with selective Trpc gene knockout (KO). In adult cerebellar brain slices, application of glutamate and the class I metabotropic glutamate receptor agonist (S)-3,5-dihydroxyphenylglycine to Purkinje neurons expressing the GCaMP5g Ca 2+ reporter demonstrated that the majority of the Ca 2+ loading in the molecular layer dendritic arbors was attributable to the TRPC3 effector channels ( Trpc3 KO compared with wildtype (WT)). This Ca 2+ dysregulation was associated with glutamate excitotoxicity causing progressive disruption of the Purkinje cell dendrites (significantly abated in a GAD67-GFP - Trpc3 KO reporter brain slice model). Contribution of the G αq -coupled TRPC channels to secondary brain injury was evaluated in a dual photothrombotic focal ischemic injury model targeting cerebellar and cerebral cortex regions, comparing day 4 post-injury in WT mice, Trpc3 KO , and Trpc1/3/6/7 quadruple knockout ( Trpc QKO ), with immediate 2-h (primary) brain injury. Neuroprotection to secondary brain injury was afforded in both brain regions by Trpc3 KO and Trpc QKO models, with the Trpc QKO showing greatest neuroprotection. These findings demonstrate the contribution of the G αq -coupled TRPC effector mechanism to excitotoxicity-based secondary brain injury expansion, which is a primary driver for mortality and morbidity in stroke, traumatic brain injury, and epilepsy.

Valuing shoreline habitats for recreational fishing - Andrew M. Scheld; Donna M. Bilkovic; Sarah Stafford; Kathleen Powers; Susanna Musick; Amanda G. Guthrie (Ocean & Coastal Management, 2024)

Impact of turbidity on the gill morphology and hypoxia tolerance of eastern sand darter ( Ammocrypta pellucida ) - Britney L. Firth; Paul M. Craig; D. Andrew R. Drake; Michael Power (Journal of Fish Biology, 2024)
Anthropogenic stressors such as agriculture and urbanization can increase river turbidity, which can negatively impact fish gill morphology and growth due to reduced oxygen in the benthic environment. We assessed the gill morphology, field metabolic rate (FMR), and two hypoxia tolerance metrics (oxygen partial pressure at loss of equilibrium, PO 2 at LOE, and critical oxygen tension, P crit ) of eastern sand darter ( Ammocrypta pellucida ), a small benthic fish listed as threatened under the Species at Risk Act in Canada, from rivers in southern Ontario. Field trials were conducted streamside in the Grand River (August 2019; mean NTU 8) and in the comparatively more turbid Thames River (August 2020; mean NTU 94) to test the effect of turbidity on each physiological endpoint. Gills were collected from incidental mortalities and museum specimens, and were assessed using hematoxylin and eosin and immunofluorescent staining. The between‐river comparison indicated that turbidity significantly increased interlamellar space and filament width but had no significant influence on other gill morphometrics or FMR. Turbidity significantly increased PO 2 at LOE (i.e., fish had a lower hypoxia tolerance) but did not significantly impact P crit . Therefore, although turbidity influences hypoxia tolerance through LOE, turbidity levels were not sufficiently high in the study rivers to contribute to measurable changes in gill morphology or metabolism in the wild. Determining whether changes in gill morphology or metabolism occur under higherturbidity levels would help resolve the ecological importance of turbidity on species physiology in urban and agricultural ecosystems.

Long-term N-addition alters the community structure of functionally important N-cycling soil microorganisms across global grasslands - Beat Frey; Barbara Moser; Bjorn Tytgat; Stephan Zimmermann; Juan Alberti; Lori A. Biederman; Elizabeth T. Borer; Arthur A.D. Broadbent; Maria C. Caldeira; Kendi F. Davies; Nico Eisenhauer; Anu Eskelinen; et al. (Soil Biology and Biochemistry, 2023)

Linking changes in species composition and biomass in a globally distributed grassland experiment - Emma Ladouceur; Shane A. Blowes; Jonathan M. Chase; Adam T. Clark; Magda Garbowski; Juan Alberti; Carlos Alberto Arnillas; Jonathan D. Bakker; Isabel C. Barrio; Siddharth Bharath; Elizabeth T. Borer; Lars A. Brudvig; et al. (Ecology Letters, 2022)
Global change drivers, such as anthropogenic nutrient inputs, are increasing globally. Nutrient deposition simultaneously alters plant biodiversity, species composition and ecosystem processes like aboveground biomass production. These changes are underpinned by species extinction, colonisation and shifting relative abundance. Here, we use the Price equation to quantify and link the contributions of species that are lost, gained or that persist to change in aboveground biomass in 59 experimental grassland sites. Under ambient (control) conditions, compositional and biomass turnover was high, and losses (i.e. local extinctions) were balanced by gains (i.e. colonisation). Under fertilisation, the decline in species richness resulted from increased species loss and decreases in species gained. Biomass increase under fertilisation resulted mostly from species that persist and to a lesser extent from species gained. Drivers of ecological change can interact relatively independently with diversity, composition and ecosystem processes and functions such as aboveground biomass due to the individual contributions of species lost, gained or persisting.

Round Goby (Neogobius melanostomus) impacts on benthic fish communities in two tributaries of the Great Lakes - Keith McAllister; D. Andrew R. Drake; Michael Power (Biological Invasions, 2022)
Numerous fish species in the Laurentian Great Lakes have been negatively impacted by the establishment of the invasive Round Goby ( Neogobius melanostomus ). However, limited understanding exists as to how Round Goby has impacted small-bodied native benthic fishes after its secondary invasion into tributaries of the Laurentian Great Lakes. To investigate Round Goby impacts on darter species (family Percidae) in tributary ecosystems, catch per unit area (CPUA) of native and non-native fishes from two riverine ecosystems in Southwestern Ontario (Ausable River, Big Otter Creek) were analyzed. Spatial analyses indicated Round Goby CPUA was highest proximate to the Great Lakes, with a sharp decline in CPUA at sites upstream from each lake (Round Goby CPUA approached zero after 18 and 14 km in the Ausable River and Big Otter Creek, respectively). There was some evidence of a negative relationship between the CPUA of Round Goby and several darter species along the tributary gradients, with moderately negative co-occurrence between Round Goby and Rainbow Darter in the Ausable River and Johnny Darter and Percidae species overall in Big Otter Creek. However, overwhelming evidence of negative associations between Round Goby and all darter species was not found. The negative relationship between the CPUA of Round Goby and some darter species was observed over similar time periods since establishment but greater spatial scales than in previous studies, and therefore has important implications for understanding the ecological impacts of Round Goby in tributary ecosystems.

Age-Related Interactions with Wind During Migration Support the Hypothesis of Developmental Learning in a Migrating Long-Lived Seabird - Kevin D. Powers; Isabeau Pratte; Robert A. Ronconi; Sarah N. P. Wong; Peter G. Ryan; Linda J. Welch; Tammy L. Silva; Kent A. Hatch; Andrew J. Westgate; David N. Wiley (Frontiers in Marine Science, 2022)
Wind patterns shape migratory pathways and detours of many procellariiform bird species that seasonally migrate between hemispheres. These seabirds are long-lived, and the period of immaturity is presumed to be a time of development and learning the environment, specifically how to use wind to their advantage. We assess how wind encountered by individual Great Shearwaters ( Ardenna gravis ) varies along the migration journey and compare responses between presumed mature and immature birds (early and late, respectively) in southbound migration and mature birds in northbound migration. We analyze modeled Argos locations from 71 individual tracks of migratory Great Shearwaters with concurrent U (East/West) and V (North/South) wind components. Migration in seabirds is well studied, but there is limited quantitative work measuring individual birds directly interacting with wind and their associated changes in flight behavior during migration. We show that Great Shearwaters made optimal use of winds, and that different age groups made decisions that exposed them to different wind constraints. Overall, Great Shearwaters derived positive responses from wind under most conditions and did not rely on a drifting strategy, which would be suggested if wind effect (difference between ground and airspeed) was predominantly positive during migrations. Instead, they appeared to use a compensating strategy to achieve an acceptable course and speed. The difference we observed in migration phenologies suggests that by migrating later, immature birds might travel the path of least resistance and experience flight conditions that are less risky furthering their ability to withstand a variety of wind conditions encountered later in life as done by adults, which migrate earlier and are subject to more variable flight conditions. We conclude that like other procellariiforms, a longer period of sexual maturity is required to enhance flight performance and mediate energy expenditure through experiential learning and increased fitness.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Nutrients and herbivores impact grassland stability across spatial scales through different pathways - Qingqing Chen; Shaopeng Wang; Eric W. Seabloom; Andrew S. MacDougall; Elizabeth T. Borer; Jonathan D. Bakker; Ian Donohue; Johannes M. H. Knops; John W. Morgan; Oliver Carroll; Mick Crawley; Miguel N. Bugalho; et al. (Global Change Biology, 2022)
Nutrients and herbivores are well‐known drivers of grassland diversity and stability in local communities. However, whether they interact to impact the stability of aboveground biomass and whether these effects depend on spatial scales remain unknown. It is also unclear whether nutrients and herbivores impact stability via different facets of plant diversity including species richness, evenness, and changes in community composition through time and space. We used a replicated experiment adding nutrients and excluding herbivores for 5 years in 34 global grasslands to explore these questions. We found that both nutrient addition and herbivore exclusion alone reduced stability at the larger spatial scale (aggregated local communities; gamma stability), but through different pathways. Nutrient addition reduced gamma stability primarily by increasing changes in local community composition over time, which was mainly driven by species replacement. Herbivore exclusion reduced gamma stability primarily by decreasing asynchronous dynamics among local communities (spatial asynchrony). Their interaction weakly increased gamma stability by increasing spatial asynchrony. Our findings indicate that disentangling the processes operating at different spatial scales may improve conservation and management aiming at maintaining the ability of ecosystems to reliably provide functions and services for humanity.

The influence of thermal cues on the reproductive phenology of S ilver S hiner, Notropis photogenis - Jacob Burbank; D. Andrew R. Drake; Michael Power (Journal of Fish Biology, 2022)
Reproductive phenology and the length of the growing season vary in response to interannual environmental variability, with implications for population dynamics of freshwater fishes. Understanding the reproductive phenology of imperilled species in relation to environmental conditions is needed to better evaluate potential responses to changing environmental conditions, estimate future population dynamics and develop comprehensive recovery strategies. We examined Silver Shiner, a species listed as “Threatened” under Canada's Species at Risk Act , during spring 2018 and 2019 to better understand the reproductive phenology of the species at the northern edge of its range in Canada. The initiation of Silver Shiner spawning occurred on the descending limb of the hydrograph and was completed before the onset of the extended period of low summer flow. In addition, both the initiation and cessation of spawning occurred in response to a cumulative growing degree day base 5 (GDD 5 ) cue, with logistic regression models indicating a 50% probability the population initiated and ceased spawning when GDD 5 reached 68°C•days and 368°C•days, respectively. Logistic regression incorporating GDD 5 effectively predicted spawning initiation and cessation, providing useful models for examining the impacts of alterations to the thermal regime on reproductive phenology and improving the ability to evaluate changes in the larval growth period. Furthermore, the models can facilitate the development of real‐time estimates of spawning activity, and therefore ensure that disturbance to the species is minimized during the sensitive reproductive period.

Temporal rarity is a better predictor of local extinction risk than spatial rarity - Peter A. Wilfahrt; Ashley L. Asmus; Eric W. Seabloom; Jeremiah A. Henning; Peter Adler; Carlos A. Arnillas; Jonathan D. Bakker; Lori Biederman; Lars A. Brudvig; Marc Cadotte; Pedro Daleo; Anu Eskelinen; et al. (Ecology, 2021)
Spatial rarity is often used to predict extinction risk, but rarity can also occur temporally. Perhaps more relevant in the context of global change is whether a species is core to a community (persistent) or transient (intermittently present), with transient species often susceptible to human activities that reduce niche space. Using 5–12 yr of data on 1,447 plant species from 49 grasslands on five continents, we show that local abundance and species persistence under ambient conditions are both effective predictors of local extinction risk following experimental exclusion of grazers or addition of nutrients; persistence was a more powerful predictor than local abundance. While perturbations increased the risk of exclusion for low persistence and abundance species, transient but abundant species were also highly likely to be excluded from a perturbed plot relative to ambient conditions. Moreover, low persistence and low abundance species that were not excluded from perturbed plots tended to have a modest increase in abundance following perturbance. Last, even core species with high abundances had large decreases in persistence and increased losses in perturbed plots, threatening the long‐term stability of these grasslands. Our results demonstrate that expanding the concept of rarity to include temporal dynamics, in addition to local abundance, more effectively predicts extinction risk in response to environmental change than either rarity axis predicts alone.

Early chemical changes during wood decomposition are controlled by fungal communities inhabiting stems at treefall in a tropical dry forest - François Maillard; Erin Andrews; Molly Moran; Dan V. Du; Peter G. Kennedy; Jennifer S. Powers; Skip J. Van Bloem; Jonathan S. Schilling (Plant and Soil, 2021)

Progress on reducing acrylamide levels in potato crisps in Europe, 2002 to 2019 - Stephen J. Powers; Donald S. Mottram; Andrew Curtis; Nigel G. Halford (Food Additives & Contaminants: Part A, 2021)

Research Priorities for Coastal Geoscience and Engineering: A Collaborative Exercise in Priority Setting From Australia - Hannah E. Power; Andrew W. M. Pomeroy; Michael A. Kinsela; Thomas P. Murray (Frontiers in Marine Science, 2021)
We present the result of a collaborative priority setting exercise to identify emerging issues and priorities in coastal geoscience and engineering (CGE). We use a ranking process to quantify the criticality of each priority from the perspective of Australian CGE researchers and practitioners. 74 activities were identified across seven categories: Data Collection and Collation, Coastal Dynamics and Processes, Modelling, Engineering Solutions, Coastal Hazards and Climate Change, Communication and Collaboration, and Infrastructure, Innovation, and Funding. We found consistent and unanimous support for the vast majority of priorities identified by the CGE community, with 91% of priorities being allocated a score of ≥ 3 out of 5 (i.e., above average levels of support) by ≥ 75% of respondents. Data Collection and Collation priorities received the highest average score, significantly higher than four of the other six categories, with Coastal Hazards and Climate Change the second ranked category and Engineering Solutions the lowest scoring category. Of the 74 priorities identified, 11 received unified and strong support across the CGE community and indicate a critical need for: additional coastal data collection including topographic and bathymetric, hydrodynamic, oceanographic, and remotely sensed data; improved data compilation and access; improved understanding of extreme events and the quantification of future impacts of climate change on nearshore dynamics and coastal development; enhanced quantification of shoreline change and coastal inundation processes; and, additional funding to support CGE research and applications to mitigate and manage coastal hazards. The outcomes of this priority setting exercise can be applied to guide policy development and decision-making in Australia and jurisdictions elsewhere. Further, the research and application needs identified here will contribute to addressing key practical challenges identified at a national level. CGE research plays a critical role in identifying and enabling social, environmental, and economic benefits through the proactive management of coastal hazard impacts and informed planning to mitigate the potential impacts of growing coastal risk, particularly in a changing climate. The prevalence and commonalities of the challenges faced by coastal communities globally due to increasing pressures from coastal hazards in a changing climate suggest that our findings will be applicable to other settings.

Global impacts of fertilization and herbivore removal on soil net nitrogen mineralization are modulated by local climate and soil properties - Anita C. Risch; Stefan Zimmermann; Barbara Moser; Martin Schütz; Frank Hagedorn; Jennifer Firn; Philip A. Fay; Peter B. Adler; Lori A. Biederman; John M. Blair; Elizabeth T. Borer; Arthur A. D. Broadbent; et al. (Global Change Biology, 2020)
Soil nitrogen (N) availability is critical for grassland functioning. However, human activities have increased the supply of biologically limiting nutrients, and changed the density and identity of mammalian herbivores. These anthropogenic changes may alter net soil N mineralization (soil net N min ), that is, the net balance between N mineralization and immobilization, which could severely impact grassland structure and functioning. Yet, to date, little is known about how fertilization and herbivore removal individually, or jointly, affect soil net N min across a wide range of grasslands that vary in soil and climatic properties. Here we collected data from 22 grasslands on five continents, all part of a globally replicated experiment, to assess how fertilization and herbivore removal affected potential (laboratory‐based) and realized (field‐based) soil net N min . Herbivore removal in the absence of fertilization did not alter potential and realized soil net N min . However, fertilization alone and in combination with herbivore removal consistently increased potential soil net N min. Realized soil net N min , in contrast, significantly decreased in fertilized plots where herbivores were removed. Treatment effects on potential and realized soil net N min were contingent on site‐specific soil and climatic properties. Fertilization effects on potential soil net N min were larger at sites with higher mean annual precipitation (MAP) and temperature of the wettest quarter (T.q.wet). Reciprocally, realized soil net N min declined most strongly with fertilization and herbivore removal at sites with lower MAP and higher T.q.wet. In summary, our findings show that anthropogenic nutrient enrichment, herbivore exclusion and alterations in future climatic conditions can negatively impact soil net N min across global grasslands under realistic field conditions. This is an important context‐dependent knowledge for grassland management worldwide.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

A framework to measure the wildness of managed large vertebrate populations - Matthew F. Child; S. A. Jeanetta Selier; Frans G. T. Radloff; W. Andrew Taylor; Michael Hoffmann; Lizanne Nel; R. John Power; Coral Birss; Nicola C. Okes; Michael J. Peel; David Mallon; Harriet Davies‐Mostert (Conservation Biology, 2019)
As landscapes continue to fall under human influence through habitat loss and fragmentation, fencing is increasingly being used to mitigate anthropogenic threats and enhance the commercial value of wildlife. Subsequent intensification of management potentially erodes wildness by disembodying populations from landscape‐level processes, thereby disconnecting species from natural selection. Tools are needed to measure the degree to which populations of large vertebrate species in formally protected and privately owned wildlife areas are self‐sustaining and free to adapt. We devised a framework to measure such wildness based on 6 attributes relating to the evolutionary and ecological dynamics of vertebrates (space, disease and parasite resistance, exposure to predation, exposure to limitations and fluctuations of food and water supply, and reproduction). For each attribute, we set empirical, species‐specific thresholds between 5 wildness states based on quantifiable management interventions. We analysed data from 205 private wildlife properties with management objectives spanning ecotourism to consumptive utilization to test the framework on 6 herbivore species representing a range of conservation statuses and commercial values. Wildness scores among species differed significantly, and the proportion of populations identified as wild ranged from 12% to 84%, which indicates the tool detected site‐scale differences both among populations of different species and populations of the same species under different management regimes. By quantifying wildness, this framework provides practitioners with standardized measurement units that link biodiversity with the sustainable use of wildlife. Applications include informing species management plans at local scales; standardizing the inclusion of managed populations in red‐list assessments; and providing a platform for certification and regulation of wildlife‐based economies. Applying this framework may help embed wildness as a normative value in policy and mitigate the shifting baseline of what it means to truly conserve a species.

Assessing the impact of charr research past, present, and future - Michael J. Hansen; Charles C. Krueger; Andrew M. Muir; Anders Klemetsen; Michael Power (Hydrobiologia, 2019)

Treatment patterns and survival differ between early-onset and late-onset colorectal cancer patients: the patient outcomes to advance learning network - Andrea N. Burnett-Hartman; J. David Powers; Jessica Chubak; Douglas A. Corley; Nirupa R. Ghai; Carmit K. McMullen; Pamala A. Pawloski; Andrew T. Sterrett; Heather Spencer Feigelson (Cancer Causes & Control, 2019)

Focal Ischaemic Infarcts Expand Faster in Cerebellar Cortex than Cerebral Cortex in a Mouse Photothrombotic Stroke Model - Nagarajesh Gorlamandala; Jasneet Parmar; Amanda J. Craig; John M. Power; Andrew J. Moorhouse; Arun V. Krishnan; Gary D. Housley (Translational Stroke Research, 2018)

The early inflorescence of Arabidopsis thaliana demonstrates positional effects in floral organ growth and meristem patterning - Andrew R. G. Plackett; Stephen J. Powers; Andy L. Phillips; Zoe A. Wilson; Peter Hedden; Stephen G. Thomas (Plant Reproduction, 2018)

Acrylamide levels in potato crisps in Europe from 2002 to 2016 - Stephen J. Powers; Donald S. Mottram; Andrew Curtis; Nigel G. Halford (Food Additives & Contaminants: Part A, 2017)

Regulation of quantal currents determines synaptic strength at neuromuscular synapses in larval Drosophila - Andrew S. Powers; Jeffrey Grizzaffi; Richard Ribchester; Gregory A. Lnenicka (Pflügers Archiv - European Journal of Physiology, 2016)

Trophic variability of Arctic fishes in the Canadian Beaufort Sea: a fatty acids and stable isotopes approach - Carolina Giraldo; Ashley Stasko; Emily S. Choy; Bruno Rosenberg; Andrew Majewski; Michael Power; Heidi Swanson; Lisa Loseto; James D. Reist (Polar Biology, 2016)

Nowhere left to go: the Sinai Hairstreak Satyrium jebelia - Andrew Power; Samy Zalat; Francis Gilbert (Journal of Insect Conservation, 2014)

The potential for indirect effects between co‐flowering plants via shared pollinators depends on resource abundance, accessibility and relatedness - Luísa Gigante Carvalheiro; Jacobus Christiaan Biesmeijer; Gita Benadi; Jochen Fründ; Martina Stang; Ignasi Bartomeus; Christopher N. Kaiser‐Bunbury; Mathilde Baude; Sofia I. F. Gomes; Vincent Merckx; Katherine C. R. Baldock; Andrew T. D. Bennett; et al. (Ecology Letters, 2014)
Co‐flowering plant species commonly share flower visitors, and thus have the potential to influence each other's pollination. In this study we analysed 750 quantitative plant–pollinator networks from 28 studies representing diverse biomes worldwide. We show that the potential for one plant species to influence another indirectly via shared pollinators was greater for plants whose resources were more abundant (higher floral unit number and nectar sugar content) and more accessible. The potential indirect influence was also stronger between phylogenetically closer plant species and was independent of plant geographic origin (native vs. non‐native). The positive effect of nectar sugar content and phylogenetic proximity was much more accentuated for bees than for other groups. Consequently, the impact of these factors depends on the pollination mode of plants, e.g. bee or fly pollinated. Our findings may help predict which plant species have the greatest importance in the functioning of plant–pollination networks.

Design, Development and Evaluation of an Inflatable Retractor for Atraumatic Retraction in Laparoscopic Colectomy - Conor O’Shea; Denis Kelliher; Emmet Andrews; Mícheál O’Ríordáin; Michael O’Shea; Timothy Power; Pádraig Cantillon-Murphy (Annals of Biomedical Engineering, 2014)

Multivariate analysis of MLH1 c.1664T>C (p.Leu555Pro) mismatch repair gene variant demonstrates its pathogenicity - M. P. Farrell; D. J. Hughes; M. Drost; A. J. Wallace; R. J. Cummins; T. A. Fletcher; M. A. Meany; E. W. Kay; N. de Wind; D. G. Power; E. J. Andrews; A. J. Green; et al. (Familial Cancer, 2013)

Acrylamide concentrations in potato crisps in Europe from 2002 to 2011 - Stephen J. Powers; Donald S. Mottram; Andrew Curtis; Nigel G. Halford (Food Additives & Contaminants: Part A, 2013)

Forest Management, Engineering, and Operations - Randy Kolka; Matt Powers; John Bradford; Brian Palik; Marty Jurgensen; Dalia Abbas; Tom Gallagher; Stephen Ambagis; Finto Antony; Lewis Jordan; Richard Daniels; Laurie Schimleck; et al. (Journal of Forestry, 2011)
9Forests represent a major global C sink, and forest management strategies that maximize carbon storage offer one avenue for mitigating increases in atmospheric carbon dioxide concentrations. Our understanding of relationships between forest management, productivity, carbon storage, and stand age, however, is limited. We established research plots in a chronosequence of thinned and unmanaged red pine stands in northern Minnesota to study patterns of carbon storage, and the major fluxes that influence carbon sequestration. We completed an inventory of all major C pools across a chronosequence of 57 red pine stands ages 9-306 years on the Chippewa National Forest in the fall of 2009. Results indicate total ecosystem C pools increase as red pine stands age for at least 150 years, and on-site C storage in thinned stands appears similar to unmanaged stands of comparable ages, despite different age-related trends in the live tree and forest floor pools. Thinned stands may have the potential to store more C than unmanaged stands in old age when C removed during harvesting is added into the total ecosystem C pool.

Effects of Human Trampling on Populations of Soil Fauna in the McMurdo Dry Valleys, Antarctica - EDWARD AYRES; JOHNSON N. NKEM; DIANA H. WALL; BYRON J. ADAMS; J. E. BARRETT; EMMA J. BROOS; ANDREW N. PARSONS; LAURA E. POWERS; BREANA L. SIMMONS; ROSS A. VIRGINIA (Conservation Biology, 2008)
Antarctic ecosystems are often considered nearly pristine because levels of anthropogenic disturbance are extremely low there. Nevertheless, over recent decades there has been a rapid increase in the number of people, researchers and tourists, visiting Antarctica. We evaluated, over 10 years, the direct impact of foot traffic on the abundance of soil animals and soil properties in Taylor Valley within the McMurdo Dry Valleys region of Antarctica. We compared soils from minimally disturbed areas with soils from nearby paths that received intermediate and high levels of human foot traffic (i.e., up to approximately 80 passes per year). The nematodes Scottnema lindsayae and Eudorylaimus sp. were the most commonly found animal species, whereas rotifers and tardigrades were found only occasionally. On the highly trampled footpaths, abundance of S. lindsayae and Eudorylaimus sp. was up to 52 and 76% lower, respectively, than in untrampled areas. Moreover, reduction in S. lindsayae abundance was more pronounced after 10 years than 2 years and in the surface soil than in the deeper soil, presumably because of the longer period of disturbance and the greater level of physical disturbance experienced by the surface soil. The ratio of living to dead Eudorylaimus sp. also declined with increased trampling intensity, which is indicative of increased mortality or reduced fecundity. At one site there was evidence that high levels of trampling reduced soil CO 2 fluxes, which is related to total biological activity in the soil. Our results show that even low levels of human traffic can significantly affect soil biota in this ecosystem and may alter ecosystem processes, such as carbon cycling. Consequently, management and conservation plans for Antarctic soils should consider the high sensitivity of soil fauna to physical disturbance as human presence in this ecosystem increases.

Effects of vitamin E deficiency on fatigue and muscle contractile properties - Jeff Coombes; Benjamin Rowell; Stephen Dodd; Haydar Demirel; Hisashi Naito; Andrew Shanely; Scott Powers (European Journal of Applied Physiology, 2002)